Sistematización del Proceso de Creación y Puesta En Escena de: La Misión P.A.-15. El Tiempo… Nunca Estuvo Tan Cerca (2016)
Taking into account the training process that has been carried out for ten semesters in the Bachelor's program in Art Education with an emphasis in Dance and Theater and experience As a teacher that the author has, the systematization of experience is chosen as the research methodological tool that allows combining practice and theory, knowledge and professional work, work and staging, in order to account not only for an experience seen from the teaching level, but with all the baggage and complement that from the theory Oscar Jara makes us in order to condense in a document a step by step of the work done in the classroom.